ANALYSIS OF DIVIDEND POLICY AND INFLUENCING FACTORS IN COMPANIES LISTED ON THE KOMPAS 100 INDEX - Sunarjanto, Nekhasius Agus; Koesdijanto, Mercy Ayu; Martono, Cyrillius (Jurnal Ekonomika dan Manajemen, 2024)
A The aim of this research is to analyze Payout ratio is influenced by cash flow, liquidity, leverage and company growth, the results of this study show that overall all these variables have a significant effect with the F test result of 0.000 which can be interpreted that the model is fit or feasible and koefisien determinan ( R2) of 39.5% although partially there are variabrl that have no effect or negative effect, namely: liquidity, and leverage The sample of this study is the Kompas 100 index listed on the IDX and uses purposive sampling totaling 28 companies